Penyusunan Masterplan Pengembangan Desa Ujungnegoro dan Depok Kabupaten Batang dengan Konsep Sustainable Community Based Tourism - Widyaningrum, Dewi Putri; Virgiawan, Adam; Hidayat, Fachrul; Ulumudin, Nur Muhammad; Kurnianingtyas, Agnesia Putri (Jurnal Pengabdian KOLABORATIF, 2025)
Ujungnegoro Village and Depok Village have great tourism potential, including marine tourism, religious tourism, agrotourism, and nature tourism. Unfortunately, the village government and the community have not been able to utilize this tourism potential optimally. This is the basis for implementing community service activities in the village. The service carried out is in the form of compiling a master plan for the development of sustainable community-based tourism in Ujungnegoro and Depok. The methods used in this service activity are literature study methods, field surveys, in-depth interviews, and SWOT analysis to produce tourism development strategies and plans. The service activity produces a masterplan book containing the village profile, potential and problems as well as village development concepts and plans. This masterplan then be an additional guideline and idea for stakeholders in developing tourism areas in Ujungnegoro Village and Depok Village by paying attention to sustainability aspects, so that it can provide benefits to the community and the environment in the long term.
Keywords: community-based tourism; masterplan; sustainability